Voting at the political fault line : California's experiment with the blanket primary - Cain, Bruce E.; Gerber, Elisabeth R., 1964- (University of California Press, 2002)
California's adoption of the blanket primary in 1996 presented a unique natural experiment on the impact that election rules have on politics. Billed as a measure that would increase voter participation and end ideological polarization, Proposition 198 placed California voters once again on the frontier of political reform.